Financial Analysis and Corporate Strategy - Chemla, Gilles (Review of Financial Studies, 2000)
Journal Article Financial Analysis and Corporate Strategy Get access Financial Analysis and Corporate Strategy. Mark Grinblatt and Sheridan Titman. Irwin/McGraw-Hill, 1998. 864 pp., $78.75 (hardcover). ISBN 0-256-09939-1. Gilles Chemla Gilles Chemla University of British Columbia THEMA(CNRS), and CEPR Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 13, Issue 1, January 2000, Pages 249–253, https://doi.org/10.1093/rfs/13.1.249 Published: 15 June 2015